A DESCRIPTIVE STUDY ON THE SEVENTH GRADE STUDENTS’ MASTERY ON PREPOSITION AT MTS MAULANA ISHAQ KABAT - Ririn Siti Nur Indah Sari; Nur Hasibin; Wageyono (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2022)
This research is a descriptive study of students’ mastery using descriptive quantative approach. This research aimed to know the Seventh grade students’ mastery on preposition at MTs Maulana Ishaq Kabat in the Academic Year 2020/2021. The researcher used test and documentation to collect the data. The indicators of the test were divided into two part; indicators of preposition of time and preposition of place. The data were analyzed bby Donald’s formula. The researcher used the The Classification of The Score Level by Depdikbud (1995). The results of the research show that the score of the seventh grade students’ mastery on using preposition of time was 47,6%. Then, the classification of the students’ mastery on using preposition of time was categorized as “poor”. Since, the score of the seventh grade students’ mastery on using preposition of place was 54,5%. Then, the classification of the students’ mastery on using preposition of place was categorized as “poor”. Therefore, the average score for preposition of time and preposition of place were 51,5% and it concluded that classification of students’ ability on using preposition was “poor”.